Mitochondrial Dysfunction in Pulmonary Hypertension - Gusty Rizky Teguh Ryanto; Ratoe Suraya; Tatsuya Nagano (MDPI AG, 2023)
Pulmonary hypertension (PH) is a multi-etiological condition with a similar hemodynamic clinical sign and end result of right heart failure. Although its causes vary, a similar link across all the classifications is the presence of mitochondrial dysfunction. Mitochondria, as the powerhouse of the cells, hold a number of vital roles in maintaining normal cellular homeostasis, including the pulmonary vascular cells. As such, any disturbance in the normal functions of mitochondria could lead to major pathological consequences. The Warburg effect has been established as a major finding in PH conditions, but other mitochondria-related metabolic and oxidative stress factors have also been reported, making important contributions to the progression of pulmonary vascular remodeling that is commonly found in PH pathophysiology. In this review, we will discuss the role of the mitochondria in maintaining a normal vasculature, how it could be altered during pulmonary vascular remodeling, and the therapeutic options available that can treat its dysfunction.